Prognostic factors in first-line atezolizumab-bevacizumab treatment of intermediate or advanced hepatocellular carcinoma - Kyowon Gu; Tae Wook Kang; Jaeseung Shin; Dong Hyun Sinn; Myung Ji Goh; Jung Yong Hong; Sangah Chi (PLoS ONE, 2026)
Purpose To analyze the prognostic factors influencing outcomes in hepatocellular carcinoma (HCC) patients initially treated with atezolizumab-bevacizumab (Ate-Bev). Methods We conducted a retrospective study on 47 treatment-naïve HCC patients (40 men; median age, 56 years) who were treated with Ate-Bev between September 2020 and July 2022 and underwent at least one response assessment based on the Response Evaluation Criteria in Solid Tumors 1.1. We evaluated the clinical variables and imaging features of pre-treatment magnetic resonance imaging (MRI). Using multivariable Cox hazard regression analysis, we analyzed prognostic factors for progression-free survival (PFS). Results During the follow-up period (range, 1.5–24.9 months), 33 patients (70.2%) experienced tumor progression. The median PFS was 4.3 months (95% confidence interval [CI], 2.8–8.5 months). Nine patients received concomitant radiotherapy. Multivariable analysis indicated that younger age (hazard ratio [HR], 0.95; 95% CI, 0.92–0.99; P = 0.013), absence of concomitant radiation therapy (HR, 0.22; 95% CI, 0.07–0.69; P = 0.009), tumor extent ≥10 cm (HR, 2.54; 95% CI, 1.17–5.55; P = 0.019), and peritumoral arterial-phase hyperenhancement on the MRI (HR, 2.15; 95% CI, 1.00–4.63; P = 0.049) were factors associated with poor PFS. Conclusions Age, concomitant radiation therapy, tumor extent, and peritumoral arterial-phase hyperenhancement on MRI were associated with PFS in patients with HCC who were initially treated with Ate-Bev.